A novel fiber–veneer-laminated composite based on tannin resin. Issue 6 (12th May 2017) - Zhou, X.; Segovia, C.; Abdullah, U. H.; Pizzi, A.; Du, G.
ABSTRACT: Natural nonwoven fiber was impregnated with a tannin resin and laminated with wood veneer for preparation of laminated composites. The tannin resin used showed a good compatibility with the natural fiber, and was easy to assemble with the wood veneers. The tannin resin penetration into the wood veneer was observed by light microscopy. The laminated composite shows very good mechanical properties and water resistance. Shear force–displacement testing demonstrates that the laminated composite had a ductile behavior under wet testing conditions. The laminated composite was prepared using 100% natural biorenewable raw materials and had good properties compared to conventional plywood bonded with synthetic resin.